Investigation of a new version of the liquid embolic agent PHIL with extra-low-viscosity in an endovascular embolization model - Vollherbst, Dominik; Otto, Ruth; Ulfert, Christian; Kauczor, Hans-Ulrich; Bendszus, Martin; Sommer, Christof-Matthias; Möhlenbruch, Markus Alfred (American journal of neuroradiology, 2018)
BACKGROUND AND PURPOSE: The type and composition of an embolic agent have a relevant influence on the performance of endovascular embolization. The aim of this study was to investigate a new version of the liquid embolic agent precipitating hydrophobic injectable liquid (PHIL) with extra-low-viscosity in an in vivo embolization model. - MATERIALS AND METHODS: Twenty-four embolization procedures were performed in the porcine rete mirabile. Eight embolizations were performed with PHIL 25% low viscosity, Squid 12, and standard PHIL 25%, respectively. Procedure time, required volume of embolic agent, visibility of the embolic agent, embolization control, embolization extent (ie, penetration of the rete mirabile), amount of reflux, and degree of embolization distal to the rete mirabile were assessed. - RESULTS: All embolic agents were adequately visible. The embolization extent was not significantly different among the 3 investigated agents; however, there was a tendency toward a higher embolization extent for PHIL 25% low viscosity (median embolization extent: 88% [PHIL 25% low viscosity]; 65% [Squid 12]; 60% [PHIL 25%]; P = .146). The amount of reflux was significantly lower for the extra-low-viscosity agents PHIL 25% low viscosity and Squid 12 compared with the standard PHIL 25% (median reflux distance: 8 mm [PHIL 25% low viscosity]; 6 mm [Squid 12]; 17 mm [PHIL 25%]; P = .011). All other embolization features did not differ among agents. - CONCLUSIONS: PHIL 25% low viscosity is a promising liquid embolic agent for endovascular embolization, featuring effective distal penetration, adequate visibility, a low amount of reflux, and good flow control.
Gesehen am 28.03.2019